Prognostic analysis of endovascular treatment for severe cerebral venous sinus thrombosis - NIE Fang; CAI Heng; TANG Wei; LI Jin-wei; FU Kai-lei; LI Zhi-qing (Chinese Journal of Contemporary Neurology and Neurosurgery, 2025)
Objective To explore the efficacy and prognosis of endovascular treatment for severe cerebral venous sinus thrombosis (CVST), providing new insights for the treatment of CVST. Methods The clinical course of 31 severe CVST patients admitted to The First Hospital of China Medical University and Shengjing Hospital of China Medical University from October 2017 to December 2024 was analyzed retrospectively. The condition of venous sinus recanalization was assessed through immediately postoperative DSA examination, and the prognosis was evaluated based on criteria such as perioperative complication rate, mortality rate during follow-up, and modified Rankin Scale (mRS) score at the last follow-up. Results A combination of multiple endovascular treatment techniques was used. Immediately after the operation, 7 patients (22.58%) achieved complete recanalization of the venous sinus and 24 patients (77.42%) achieved partial recanalization. The incidence of perioperative complication rate was 6.45% (2/31), and there was no new cerebral infarction. The average follow-up period was (6.60 ± 3.40) months. No deaths were reported during the follow-up period. At the last follow-up, 28 patients (90.32%) had a good prognosis (mRS score ≤ 2). Conclusions Endovascular treatment can effectively reduce the mortality rate and improve the prognosis of patients with severe CVST, but individualized assessment is required, and indications must be strictly controlled.